Political environment, financial intermediation costs, and financing patterns - Gungoraydinoglu, Ali; Çolak, Gönül; Öztekin, Özde (Journal of Corporate Finance, 2017)
Political environment is an important determinant of financial intermediation costs, which eventually affects the external financing patterns of firms. Political gyrations create policy uncertainty, which increases the information risk, weakens the investor demand, and reduces the offer size. This raises the securities' placement costs for the financial intermediaries, who pass on these costs to the issuing firms in the form of higher underwriter spreads. The issuance costs for new equity and debt capital increase, leading to lower leverage. Simultaneous equation analysis of financing, investment, and cash policies reveals that this channel is distinct from previously documented effects of policy uncertainty on corporate outcomes.